2018
DOI: 10.1194/jlr.m085647
|View full text |Cite
|
Sign up to set email alerts
|

NT-PGC-1α deficiency decreases mitochondrial FA oxidation in brown adipose tissue and alters substrate utilization in vivo

Abstract: Transcriptional coactivator PPAR γ coactivator (PGC)-1α and its splice variant N-terminal (NT)-PGC-1α mediate transcriptional regulation of brown adipose tissue (BAT) thermogenesis in response to changes in ambient temperature. PGC-1α is dispensable for cold-induced BAT thermogenesis as long as NT-PGC-1α is present. However, the functional significance of NT-PGC-1α in BAT has not been determined. In the present study, we generated NT-PGC-1α mice to investigate the effect of NT-PGC-1α deficiency on adaptive BAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We previously showed that NT-PGC-1α ablation decreases fatty acid oxidation in BAT 12 . Thus, we hypothesized that NT-PGC-1α −/− mice would be more prone to diet-induced obesity under high fat dietary conditions.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We previously showed that NT-PGC-1α ablation decreases fatty acid oxidation in BAT 12 . Thus, we hypothesized that NT-PGC-1α −/− mice would be more prone to diet-induced obesity under high fat dietary conditions.…”
Section: Discussionmentioning
confidence: 93%
“…The total number of animals used in this study was determined using the G*Power (v3.1.9.2) 40 with a power set at 80% and a significance level set at 0.05 for detecting a difference between two groups. NT-PGC-1α −/− mice have been described previously 12 . All mice were housed on a 12-h light/12-h dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Locomotor activity and food intake over the 6-day period did not differ between the genotypes ( Supplementary Figures 1A , B ). It is well documented that CL316243-mediated activation of brown and beige adipose tissue upregulates genes involved in mitochondrial biogenesis, thermogenesis, mitochondrial electron transport activity, fatty acid oxidation, lipid metabolism, and glucose metabolism ( Yu et al, 2002 ; Chang et al, 2012 ; Mottillo et al, 2014 ; Hao et al, 2015 ; Kim et al, 2018 ). Thus, we examined the gene expression profiles of BAT and IWAT from Sgk2 +/+ and Sgk2 −/− mice treated with CL316243 for 10days.…”
Section: Resultsmentioning
confidence: 99%
“…▶table 1 illustrates the effect of BAT activation via cold exposure and exercise on UCP1 and PGC-1α. In rodents, exposure to 4 °C increased UCP1 mRNA consistently after 3-24 h [17,[27][28][29][72][73][74][75][76][77][78][79][80], an effect that is maintained for up to 7 days [47,72,[81][82][83]. Chronic cold exposure for 4-5 weeks resulted in a new acclimation state characterized by elevated UCP1 content, demonstrating that cold exposure robustly increases UCP1 content in rodent BAT [47,84].…”
Section: Activation Of Ucp1mentioning
confidence: 99%